Mainstreaming women farmers: Innovations and approach - Munshi, Sugandha (Springer, 2023)
Mainstreaming women in agriculture is the need of the hour and its imperative to bring and discuss innovations and approaches which can accelerate the pace of it. In spite of her back-breaking work women farmers remain invisible and is aspiring for her identity as a farmer. There are various challenges which is in the ecosystem of a woman farmer ranging from lack of an equal level playing field with that of men, identity crisis, lack of gendered extension system, lack of control over resources like land, input etc. which needs a planned strategy and intervention aiming to reduce the gaps. There are innovations at the grassroots operational which helps in creating a conducive environment for women in agriculture to initiate and participate in the agriculture development. Self Help groups (SHGs) working in India have brought a momentum to the process of mainstreaming women in agriculture with the provision of a platform led by women to learn new technologies, implement the learnings on their farm and also creating larger scope for women-led entrepreneurship in farming’s. At the grassroots, village level an inclusive extension system where a right number of women officials works helps in reaching out to women farmers more easily owing to the social norms where interaction between women is an acceptable norm rather men interacting with women. In the world of new normal now, “Information, Education and Communication” (IEC) materials have a huge role to play as far as instilling the right approach towards tackling the gender biases existing in the field of agriculture is concerned. As far as the communication tools and materials are concerned, we need to pull our socks for making it inclusive.